Implementasi Sistem Informasi dalam Upaya Optimalisasi Pengelolaan Laboratorium Komputer Jurusan Teknik Informatika Politap - Darmanto, Darmanto; Wahyudi, Eka; Pratiwi , Mega; Novita Sari , Cahya (Applied Information Technology and Computer Science (AICOMS), 2022)
Laboratories in higher education have a very important role in achieving organisational goals, namely to produce graduates who are noble, ethical, have superior competence, and are competitive, in addition to producing research and community service based on applied technology to improve the welfare of society. In fact, there are still many laboratories in higher education that have not been managed properly so that their use cannot function optimally. The purpose of this research is to create a computer laboratory management information system for the Informatics Engineering Department of Politap. The method in system development uses agile software development scrum model (agile software development) while in the system testing stage the black box testing method is used. The results of the research obtained in the form of an information system with modules including inventory management of practical tools and materials, scheduling management, loan management, laboratory technician task management, care and maintenance management. With the implementation of information systems, it can facilitate technicians, laboratory heads and department heads to manage laboratories so that they can be used optimally.